Influence of trace Zr on the microstructure and elevated temperature properties of an Al–Si–Cu–Ni–Mg piston alloy. (22nd February 2019) - Gao, Tong; Ringer, Simon; Liu, Guiliang; Liu, Xiangfa
Abstract: The effect of trace Zr on the microstructure, precipitates and mechanical properties on an Al–12.6 wt% Si–4 wt% Cu–1.5 wt% Ni–1.5 wt% Mg piston alloy was studied in this paper. The α –Al dendrites are refined, resulting in a more compact distribution of primary intermetallics. The main precipitates are S (Al2 CuMg) after T6 heat treatment. It was found that the S precipitates are denser and finer in the Zr–contained alloy whereas L12 –ZrAl3 particles also precipitate. The hardness and elevated temperature tensile strength of the piston alloy were both improved, indicating the positive effect of trace Zr.